Jewish National Movement in Lithuania For the Right to Leave to Israel - Tatarūnas, Linas (Genocidas ir rezistencija, 2002)
After the reoccupation of Lithuania (1944) the Lithuanian people began a struggle against the sovietization of the country. This struggle had lasted for more than ten years. The armed resistance was suppressed by the Soviets only by the middle of the 50s. Enormous loses in nation (approximately 0,5 million residents) paralyzed the resistance for a decade and a half until the beginning of the 70s. (The resistance became more passive since then). In the middle of the 70s the actions of Lithuanian Jews and Russian Jews grew into a dissident movement for the right to leave to Israel. The struggle of the Lithuanian Jews for the right to emigrate fell in alongside with the common resistance movement against the Soviet regime in Lithuania. The initial activities of the Jews in Lithuania for the right to emigrate from the USSR were petitions to the authorities, and both individual and collective open letters. In addition to petitions and letters, the most popular way of Jewish movement manifestation in Lithuania was demonstrations. To compare the Jewish dissident movement in Russia and Lithuania the latter had specific features as the Lithuanian Jews refused to have relations with the national underground. There was no close connection between Lithuanian and Jewish dissidents. At the end of the 70s and beginning of the 80s the Jews developed special struggle strategy to leave for Israel. On the 22 June 1971 for the first time the Jews hunger-struck in Moscow. Thirty Jews from the Baltic States participated in the strike. Not only the Jews took part in the dissident Jewish movement. The actual goal the majority of the movement strived for was not Israel, but the emigration from the USSR. At the time Helsinki groups were the first associations to protect human rights, therefore the Jewish activists on equal rights with the defenders entered the associations. The aim to emigrate determined the different psychology of the Jewish movement. While Lithuanian dissidents struggled for the restoration of the independence of the Lithuanian State and the Russian dissidents fought for democracy, the Jews only wished to have a right to emigrate from the USSR. At the end of the 70s and beginning of the 80s the emigration of Jews from Lithuania and all the Soviet Union was suppressed. Since 1982 the Soviet authorities proceeded with their conventional policy, namely, to keep the frontier closed". Unfortunately, thousands of people who had submitted applications for the emigration remained living in the USSR under tragic conditions. Nevertheless, it is worth mentioning that many Soviet Jews who had been attempting to emigrate from Lithuania finally were issued Israel visas and successfully went abroad in the period of 1970–1980.
Keywords: Soviet Lithuania; Jews; emigration; resistance; USA; Israel